Wireless power transfer for electric vehicle charging - Ahmad, A. M.; Khalifa, Othman Omran (AIP Publishing, 2020)
Wireless power transfer is becoming a main concern to everyone staring with the producer to whatever the product to the user and that’s is the reflection of the usage of any wired supported product. However, due to oil rarefaction and gas emission restrictions, there is a growing interest all over the world for introducing electrical propulsion for ground transportation. Hybrid electrical vehicles are a first step for this energy transition, changing oil consumption in internal combustion engine to clean electric consumption in full electric vehicle. In this paper, the techniques of Wireless Power Transfer is discussed and how its related to the Wireless Power Transfer for electric vehicle is presented. A dynamic Inductive power transfer method is proposed. A simulation and experimental implementation were conducted. The testing were conducted with different situations in terms of distance and alignment. the wireless charging was achieved an efficiency of 90%.